(untitled) (Journal of Pharmaceutical Negative Results, 2022)
AIM: To check the effect of torsional preloading of heat-treated files on the cyclic fatigue resistance in simulated 90o canal curvature. METHODOLOGY: Eight Hyflex EDM, size 20.04, 25mm and eight Hyflex CM, size 20.04, 25 mm were selected for the study. Four subgroups of eight new files from each brand were created. Three groups were subjected to various numbers of rotary (1, 5 and 10) cycles and autoclave sterilisation cycles in a 45°-curve-simulated acrylic canal. A single group was designated as the control group and was not gone through any rotational cycles or autoclave sterilisation. Then, cyclic fatigue was conducted to the preloaded files using a specially created experimental setup. The fixed shaping block was manufactured of concave, tempered steel with a radius of curvature of 5 mm and a constant degree of curvature of 90°. In a metal block with a simulated 90° bend, NiTi files were tested until they fractured. The number of cycles to failure (NCF) for each instrument was then calculated. To compare the cyclic fatigue of various rotary files, a statistical analysis using the one-way ANOVA test and the post hoc Tukey's test was conducted. RESULTS: In cyclic fatigue fracture test, Hyflex EDM showed higher flexibility with highest value of 16.4±1.35 s compared to Hyflex CM with the value of 13.1±1.45 s. CONCLUSIONS: EDM (HyFlex EDM) wire technology showed better cyclic fatigue resistance than CM wire (Hyflex CM)